Analysis of determinants of purchase decision: The role of element of package, product quality and perceived value - Mariana Febrianti, R. Adjeng; Andhika, Raihan (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
This study aims to analyze the effect of the element of package, product quality and perceived value on consumer purchasing decisions. This research was conducted using quantitative methods, and the data in the study were collected through surveys. The population in this study were consumers of Batik Komar Bandung products, with a total sample of 110 respondents. The questionnaire in this study was measured with a Likert scale to determine respondents' perceptions regarding the elements of package, perceived value, and purchasing decisions made by consumers. The data obtained were processed using multiple regression analysis with SPSS 23 software. The results of this study indicate if there is a positive influence from the element of package, productquality and perceived value on consumer purchasing decisions on Batik Komar Bandung products. The findings of this study can provide insight for managers and owners of IKM, especially those of UKM Batik Komar Bandung, so that they can further improve consumer purchasing decisions and achieve higher profits.